Al-Tadhkira fī ʿilm al-hayʾa - Ṭūsī, Naṣīr al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
Naṣīr al-Dīn Ṭūsī (d. 672/1274) was an influential philosopher, theologian, mathematician and astronomer, besides being the first director of the famous observatory at Marāghah near Tabriz as well as a man of politics. The author of a large number of works, he is especially famous for such treatises as his Tajrīd al-iʿtiqād on theology; the Zīj-i Īlkhānī on astronomy; the Ḥall mushkilāt al-Ishārāt ; his influential commentary on Avicenna's (428/1037) Kitāb al-ishārāt wal-tanbīhāt on philosophy and logic; and his Akhlāq-i Nāṣirī on ethics. Another famous work is his Tadhkira fī ʿilm al-hayʾa published here. As stated by the editor, this is one of the most important and influential astronomical works written in the pre-modern Islamic world. It belongs to the second phase of Ṭūsī's academic career and constitutes a synthesis between two earlier works by him, written when he was still working for the Nizārī Ismailis. Arabic text and apparatus, Persian introduction translated from the English edition.